MicroRNA analysis of childhood atopic dermatitis reveals a role for miR‐451a. (27th July 2020) - Nousbeck, J.; McAleer, M.A.; Hurault, G.; Kenny, E.; Harte, K.; Kezic, S.; Tanaka, R.J.; Irvine, A.D.
Summary: Background: MicroRNAs (miRNAs), important regulators of gene expression, have been implicated in a variety of disorders. The expression pattern of miRNAs in paediatric atopic dermatitis (AD) has not been well studied. Objectives: We sought to investigate miRNA expression profiles in different blood compartments of infants with AD. Methods: Small RNA and analysis with the HTG EdgeSeq system were performed to identify differentially expressed miRNAs in peripheral blood mononuclear cells (PBMCs) and plasma of infants with AD vs. age‐matched healthy controls, with reverse transcription quantitative real‐time polymerase chain reaction (RT‐qPCR) used for validation and measurement of miRNA targets. Logistic regression models with area under the receiving operating characteristic estimation was used to evaluate the diagnostic potential of chosen miRNAs for AD. Results: RNA sequencing was performed to access miRNA expression profiles in paediatric AD. We identified 10 differentially expressed miRNAs in PBMCs and eight dysregulated miRNAs in plasma of infants with AD compared with controls. Upregulated miRNAs in PBMCs included miRNAs known to be involved in inflammation: miR‐223‐3p, miR‐126‐5p and miR‐143‐3p. Differential expression of only one miRNA, miR‐451a, was observed in both PBMCs and plasma of children with AD. Dysregulation of three miRNAs (miR‐451a, miR‐143‐3p and miR‐223‐3p) was validated in larger numbers of samples and miR‐451a was identified as a predictive biomarker for the early diagnosis of the disease. Experimentally verified targets of miR‐451a, interleukin 6 receptor (IL6R) and proteasome subunit beta type‐8 (PSMB8), were increased in patients with AD, negatively correlated with miR‐451a levels and upregulated following inhibition of miR‐451a in PBMCs. Conclusions: In infants with AD, a distinct peripheral blood miRNA signature is seen, highlighting the systemic effects of the disease. miR‐451a is uniquely expressed in different blood compartments of patients with AD and may serve as a promising novel biomarker for the early diagnosis of AD. Abstract : What is already known about this topic? Atopic dermatitis (AD) is a common childhood disease with a complex pathogenesis. miRNA expression studies to date have been performed mainly on samples from adults or older children. What does this study add? miRNAs are differentially expressed in both plasma and peripheral blood cells of infants with AD. miR‐451a may serve as a potential noninvasive biomarker for paediatric AD. What is the translational message? miR‐451a, uniquely expressed in different blood compartments of paediatric patients with AD, has potential for use as a noninvasive biomarker to diagnose the disease. Better understanding of miR‐451a activity may provide better insights into AD pathogenesis. Linked Comment: Polak. Br J Dermatol 2021; 184:391–392 . Plain language summary available online